La renaissance du Jardin des Plantes de Montpellier. Passé, présent et avenir du plus ancien jardin botanique de France - François Michaud (In Situ)
The Jardin des Plantes in Montpellier is the oldest botanical garden in France. It has remained a University property since its creation over four centuries ago and is one of the few gardens to have resisted the crush of urban development. In recognition of its importance, the Gardens’ classification as a protected nature preserve ("Site classé" - 1982) and among the French National Monuments (1992) paved the way for funding an expansive restoration effort. The third millenium will restore the Jardin des Plantes to its original glory, when it elevated botanics – initially mostly confined to medical purposes – to the rank of a science. This unique site will also return to its public service role, illustrating the relationship between man and plants and the now critical concerns of biodiversity and sustainability.